Experience of Legal Regulation of Public-Private Partnerships Abroad and in Uzbekistan (Eurasian Journal of Humanities and Social Sciences, 2023)
For the stable economic and sustainable development of the country, it is very important that the state has sufficient opportunities and means to effectively implement large economically significant projects. and infrastructure projects. Considering that the state budget will not always be able to fully cover all these costs, it has to use various mechanisms, among which public-private partnership has shown its relevance today. As part of the use of this mechanism, it is important to develop not only the principles of economics and politics, but also to improve the legal side of this process.